2020
DOI: 10.1186/s12872-020-01371-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the accuracy of two point-of-care haemoglobin meters used in sub-Saharan African population: a cross-sectional study

Abstract: Background: Point-of-care haemoglobin meters are attractive solutions to improve timely diagnosis of anaemia in resource-limited settings. However, concerns regarding the accuracy of these meters may affect their adoption. The accuracy of two hand-held point-of-care haemoglobin meters was evaluated against reference full blood count analyser. Methods: This was a hospital-based cross-sectional study conducted at the Douala General hospital, Cameroon. Two handheld haemoglobin meters were assessed: Urit12® (URIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 15 publications
(22 reference statements)
0
24
0
Order By: Relevance
“…The use of hemoglobin meters in resource limited settings might offer enormous advantages compared to a reference analyser. But extreme caution and clinical judgment are imperative to complement their use (Choukem et al, 2020). HB meter is a digital multicheck medical device that is used to measure hemoglobin where its use is accurate, does not hurt, anytime and anywhere can be done.…”
Section: Resultsmentioning
confidence: 99%
“…The use of hemoglobin meters in resource limited settings might offer enormous advantages compared to a reference analyser. But extreme caution and clinical judgment are imperative to complement their use (Choukem et al, 2020). HB meter is a digital multicheck medical device that is used to measure hemoglobin where its use is accurate, does not hurt, anytime and anywhere can be done.…”
Section: Resultsmentioning
confidence: 99%
“…No POC(Hb) T showed excellent diagnostic accuracy across all measurements and therefore may not meet all ASSURED criteria [12]. Five studies reported overestimation of Hb concentration in eight POC(Hb)Ts (Table 2) [15,29,32,49,58]. This is vital since it could result in misclassification of severity of anaemia and therefore prevent truly eligible children from receiving a lifesaving transfusion or appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies (32%) reported challenges to POC(Hb)T use [13,15,19,29,31,32,47,49,50,54,55,58,60]. Overestimation of Hb concentration (n = 5) and errors in sampling and environmental factors (n = 5) were the most frequently reported challenges.…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations